Wave dynamics features in a sea ice area - Bukatov, A. A.; Bukatov, A. E.; Zharkov, V. V.; Zav’yalov, D. D. (Ukrainian Antarctic Journal, 2003)
On a base of developed hydrodynamic models the reflecting capacities of edges, cracks and ice field breaks are studied when the surface waves pass through them. It was investigated the ice flexural rigidity and compression effects on the spatial distribution of wave disturbance amplitudes and bend stresses of the ice cover on both sides of the examined horizontal non-uniformity. Assessment of the ice breaking possibility within the edge-side zones was made. The surface wave propagation from the basin deep-water area through the bottom’s step into the area of the finite depth is investigated. The spatial and temporal features of the formed dynamic frontal zones on both sides of the step are revealed. The dependence of the basin surface displacement amplitudes and wave current velocities on the ice thickness, incident wave periods, and depth of the step occurrence, is studied. The three-dimensional bending vibrations of floating ice cover induced by a moving vortex formation are studied. Dependence of the amplitude-phase vibration characteristics on the ice rigidity in bending, angular velocity and forward speed of the vortex is investigated. Spatial distribution of the flexural-gravity disturbances both in front of the moving pressure region and in the back wake is analyzed. A mathematical model of the non-linear dynamics of surface waves of finite amplitude in the ice floes seas was developed involving the method of multiscale expansions. Using the model, it was studied the dependence of the amplitude-phase structure of disturbances, formed by the propagating non-linear periodic waves, on the basin depth, ice thickness and non-linearity of its vertical acceleration, frequency and steepness of initial wave harmonics. The ice Stokes drift velocity was estimated as well as the ice induced non-linear mass transport analyzed.